Nutrition - related factors and binge eating behaviour in a sample of Malaysian university students - Mohd Yusof, Barakatun Nisak; Chin, Yit Siew; Yen, Hui Thu; Ellin, Kiung; Abdul Ghani, Rohana; Motallib, Adham; Hamdy, Osama (Penerbit Universiti Kebangsaan Malaysia, 2019)
Binge eating (BE) behaviour is associated with obesity and eating disorders. This cross-sectional study investigates BE behaviour and its relationship with nutrition-related factors among university students. A total of 170 (69% females) university students in Malaysia aged 19 to 24 years participated in this study. BE behaviour was assessed with the use of Binge Eating Scale (BES) questionnaire. Socio-demographic background and nutritional status (anthropometric measurements, body mass index (BMI) and dietary intake) were also measured. BE behaviour reported by 10% percent of the participants. BE behaviour was associated with increased energy intake, elevated BMI and sex (Adjusted R2 = 0.116, p < 0.001). Differences in sex-specific factors in predicting the risk of BE behaviour were evident. In male participants, an increased in energy intake, elevated BMI and had a higher waist circumference associated with the risk of BE behaviour (Adjusted R2 = 0.411, p < 0.001). In female participants, only a higher waist circumference associated with BE behaviour (Adjusted R2 = 0.028, p < 0.05). The finding suggests that understanding sex-specific factors are necessary to prevent BE. These are the potential targets for tailored eating behaviour intervention among university students.